Improving reading comprehension through directed reading-thinking activity (DRTA) strategy - Erliana, Santi (Journal on English as a Foreign Language (JEFL), 2011)
This paper highlights the findings of a study which was undertaken at Islamic State College of Palangka Raya. The aim of the study was to describe how the Directed Reading Thinking Activity (henceforth DR-TA) strategy can improve reading comprehension. The data were taken from observation, field notes, questionnaire, and achievement test. The result reveals that the DR-TA not only improves studentsâ comprehension but also increases their motivation in learning.Â